Functionally interacting telomerase RNAs in the yeast telomerase complex - Prescott, John (Cold Spring Harbor Laboratory Press, 1997)
The ribonucleoprotein (RNP) enzyme telomerase from Saccharomyces cerevisiae adds telomeric DNA to chromosomal ends in short increments both in vivo and in vitro. Whether or not telomerase functions as a multimer has not been addressed previously. Here we show, first, that following polymerization, the telomerase RNP remains stably bound to its telomeric oligonucleotide reaction product. We then exploit this finding and a previously reported mutant telomerase RNA to demonstrate that, unexpectedly, the S. cerevisiae telomerase complex contains at least two functionally interacting RNA molecules that both act as templates for DNA polymerization. Here, functional telomerase contains at least two active sites.